Nutrient enrichment is related to two facets of beta diversity for stream invertebrates across the united states - Bini, Luis Mauricio; Landeiro, Victor Lemes; Padial, Andre Andrian; Siqueira, Tadeu [UNESP]; Heino, Jani (Ecological Soc Amer, 2014)
Beta diversity, the spatial or temporal variability of species composition, is a key concept in community ecology. However, our ability to predict the relative importance of the main drivers of beta diversity (e. g., environmental heterogeneity, dispersal limitation, and environmental productivity) remains limited. Using a comprehensive data set on stream invertebrate assemblages across the continental United States, we found a hump-shaped relationship between beta diversity and within-ecoregion nutrient concentrations. Within-ecoregion compositional dissimilarity matrices were mainly related to environmental distances in most of the 30 ecoregions analyzed, suggesting a stronger role for species-sorting than for spatial processes. The strength of these relationships varied considerably among ecoregions, but they were unrelated to within-ecoregion environmental heterogeneity or spatial extent. Instead, we detected a negative correlation between the strength of species sorting and nutrient concentrations. We suggest that eutrophication is a major mechanism disassembling invertebrate assemblages in streams at a continental scale.
Keywords: assemblage structure; beta diversity; continental United States; ecoregions; environmental heterogeneity; eutrophication; metacommunity; nutrient concentration; spatial extent; species sorting; stream invertebrate; Wadeable Streams Assessment